The Effect of Entrepreneurship Learning, Entrepreneurial Knowledge, Industrial Work Practice Experience, and Family Environment on Entrepreneurial Interest with Self-Efficacy as an Intervening Variable for State Vocational Students in Makassar City - Tahir, Sumiati; Thamrin Tahir; Muhammad Aziz; Rahmatullah, Rahmatullah; Mustari, Mustari; Hamsu Abdul Gani (International Journal of Education, Vocational and Social Science, 2024)
This study aims to determine the effect of entrepreneurship learning, entrepreneurship knowledge, industrial work practice experience and family environment on entrepreneurial interest either directly or indirectly through self-efficacy as an intervening variable. The population in this study were 3530 students of class XII SMK Negeri Makassar City and a sample of 845 students slovin formula with a standard error of 3% by Cluster Random Sampling method. The data collection method used a questionnaire. Data analysis using descriptive analysis, path analysis, and sobel test using SPSS and Smart PLS software. The results showed that 1) directly, there is a positive and significant effect of entrepreneurship learning, entrepreneurial knowledge and family environment on self-efficacy 2) directly, there is a positive and significant effect of entrepreneurship learning, entrepreneurial knowledge, self-efficacy and on entrepreneurial interest, 3) indirectly, there is a positive and significant effect of entrepreneurship learning, entrepreneurial knowledge and family environment on entrepreneurial interest through self-efficacy. However, industrial work practice experience is not significant on self-efficacy and entrepreneurial interest of vocational students